Cement burn: an occupational disease with favorable outcome. Case report. Issue 5 (22nd December 2015) - Chiriac, Anca; Podoleanu, Cristian; Moldovan, Cosmin; Stolnicu, Simona
Abstract: We present the case of a 54‐year‐old patient with a thermal cement burn. This rare case is a localised occupational chemical cement burn on the lower limbs, with no systemic involvement and favourable outcome. The lesion was induced by prolonged contact of the skin with cement and water during hot summer days.